2015
DOI: 10.1016/j.jaapos.2015.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Higher-order aberrations and best-corrected visual acuity in Native American children with a high prevalence of astigmatism

Abstract: Purpose To determine whether higher-order aberrations (HOAs) in children from a highly astigmatic population differ from population norms and whether HOAs are associated with astigmatism and reduced best-corrected visual acuity. Methods Subjects were 218 Tohono O’odham Native American children 5–9 years of age. Noncycloplegic HOA measurements were obtained with a handheld Shack-Hartmann sensor (SHS). Signed (z06s to z14s) and unsigned (z06u to z14u) wavefront aberration Zernike coefficients Z(3,−3) to Z(4,4)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
0
6
1
Order By: Relevance
“…However, persistent infantile astigmatism is associated with increased astigmatism and myopia during school years (30)(31)(32)(33). In this case, our data do not match those obtained by Miller et al (34), who found that elevated higher-order aberrations to astigmatism and unsigned spherical aberration were minimal and not clinically significant in native American children. It is possible that this difference is due to ethnic differences between our study cohort from Italy and cohorts from other nations or regions.…”
Section: Discussioncontrasting
confidence: 99%
“…However, persistent infantile astigmatism is associated with increased astigmatism and myopia during school years (30)(31)(32)(33). In this case, our data do not match those obtained by Miller et al (34), who found that elevated higher-order aberrations to astigmatism and unsigned spherical aberration were minimal and not clinically significant in native American children. It is possible that this difference is due to ethnic differences between our study cohort from Italy and cohorts from other nations or regions.…”
Section: Discussioncontrasting
confidence: 99%
“…We used multiple regression analyses to identify the factors associated with corneal SAs. It was no surprise to find that astigmatism did not contribute to either the anterior or total corneal SA in the regression models because Miller et al reported that they observed no association between elevated astigmatism and SA [32]. The negative coefficients for axial length in the regression were consistent with the decreasing trend in SA values as the axial length increased in patients with astigmatism of 1-2 D (axial length < 20 mm was omitted from the analysis because the population was small).…”
Section: Discussionmentioning
confidence: 99%
“…1 The prevalence of astigmatism (>1.00 D) varies over a wide range through the different studies, from 17% to 63%. 2 – 7…”
Section: Introductionmentioning
confidence: 99%
“…1 The prevalence of astigmatism (>1.00 D) varies over a wide range through the different studies, from 17% to 63%. [2][3][4][5][6][7] The origin of ocular astigmatism is not always purely corneal. 8 Two components of astigmatism can be individually measured: autorefraction astigmatism (ARA) and anterior corneal astigmatism (ACA), which arises from the anterior corneal surface.…”
Section: Introductionmentioning
confidence: 99%